2018
DOI: 10.3390/app8030351
|View full text |Cite
|
Sign up to set email alerts
|

A Vector Printing Method for High-Speed Electrohydrodynamic (EHD) Jet Printing Based on Encoder Position Sensors

Abstract: Electrohyrodynamic (EHD) jet printing has been widely used in the field of direct micro-nano patterning applications, due to its high resolution printing capability. So far, vector line printing using a single nozzle has been widely used for most EHD printing applications. However, the application has been limited to low-speed printing, to avoid non-uniform line width near the end points where line printing starts and ends. At end points of line vector printing, the deposited drop amount is likely to be signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The speed of the translational stage on which the substrate sits can aid in achieving high‐quality continuous printing. This has been studied in‐depth by Phung et al [ 91,93,128 ] They demonstrated that if the speed is too slow, excessive deposition occurs. However, if the speed is too great, then discontinuities occur due to the deposition being too slow.…”
Section: System Parametersmentioning
confidence: 99%
“…The speed of the translational stage on which the substrate sits can aid in achieving high‐quality continuous printing. This has been studied in‐depth by Phung et al [ 91,93,128 ] They demonstrated that if the speed is too slow, excessive deposition occurs. However, if the speed is too great, then discontinuities occur due to the deposition being too slow.…”
Section: System Parametersmentioning
confidence: 99%
“…EHD printing can generate a droplet much smaller than a nozzle diameter, so higher resolution printing is feasible as compared with inkjet printing even though it has a limitation of low-speed and non-uniform line printing. A new vector printing method for EHD printing was proposed by Phung et al in order to overcome this limitation and obtain uniform EHD-printed lines [3]. They developed an encoder processing unit as well as a built-in computer-aided design software to consider both the acceleration or deceleration region and the constant speed region of the moving stage.…”
Section: Printed Electronicsmentioning
confidence: 99%
“…Chang et al 19 developed an interlace rotation algorithm that can plan the printing path and nozzle ejection action by rotating the printhead angle, and the results showed that the printing resolution can be continuously adjusted from 100 dots per inch (DPI) to 5080 DPI. Phung et al 20 designed an encoder processing unit and a vector printing algorithm to plan X–Y printing motions and nozzle ejection actions by producing droplets at an equally spaced distance to prevent a nonuniform linewidth near the endpoints where line printing starts and ends. Kim et al 21 presented an algorithm to redefine the printed image resolution according to the pixel pitch of OLEDs and then planned the printing process according to a bitmap pattern.…”
Section: Introductionmentioning
confidence: 99%